Distribution pattern of threatened plants in Qakh district (Azerbaijan): environmental factors affecting and prediction of the potential distribution - Ibrahimova, Aida G. (Journal of the Belarusian State University. Ecology, 2020)
Floristic investigations are necessary for the assessment of the current diversity status and conservation of biodiversity on a global and national scale. Recently, biodiversity studies are taken up on different multidisciplinary methods and measurements. Qakh district, which is located in the northwestern part of Azerbaijan demonstrates an extremely diverse local flora, and it presents about 25 % of all plant species of the Caucasus. In the present study for the first time, we compiled a checklist of threatened plants diversity of the study area, the patterns of species range depending on the altitudinal gradient, to determine concentration areas with rich biodiversity and endemism. Besides, selected 15 threatened species were investigated based on multivariate statistical analysis (CCA) based on six environmental factors (temperature, prediction, carbon dioxide, humidity, altitude, and slope). For the first time, we used the Maximum Entropy Modeling (Maxent) approach of the Species Distribution Modelling (SDM) for Qakh district, to predict the potential distribution of Platanthera chlorantha (Custer) Rchb. (Orchidaceae), Ophrys oestrifera M. Bieb. (Orchidaceae) and Castanea sativa Mill. (Fagaceae). The key findings of the study were that the north and northeastern parts were identified as main rich centers of biodiversity and endemism in the study area. As a result of the statistical analysis, it became clear that as the elevation increases the richness of endemism is also raising. For many plants, the temperature and the humidity were indicated as the significant environmental variables that influenced the species abundance.
Keywords: endemism; species richness; CCA; red list species; species distribution modeling; conservation